Intra-subject variability in oscillometry correlates with acute rejection and CLAD post-lung transplant - Vasileva, Anastasiia; Hanafi, Nour; Huszti, Ella; Matelski, John; Belousova, Natalia; Wu, Joyce K. Y.; Martinu, Tereza; Ghany, Rasheed; Keshavjee, Shaf; Tikkanen, Jussi; Cypel, Marcelo; Yeung, Jonathan C.; et al. (Frontiers in Medicine, 2023)
Background: Chronic lung allograft dysfunction (CLAD) is the major cause of death post-lung transplantation, with acute cellular rejection (ACR) being the biggest contributing risk factor. Although patients are routinely monitored with spirometry, FEV1 is stable or improving in most ACR episodes. In contrast, oscillometry is highly sensitive to respiratory mechanics and shown to track graft injury associated with ACR and its improvement following treatment. We hypothesize that intra-subject variability in oscillometry measurements correlates with ACR and risk of CLAD. Methods: Of 289 bilateral lung recipients enrolled for oscillometry prior to laboratory-based spirometry between December 2017 and March 2020, 230 had ≥3 months and 175 had ≥6 months of follow-up. While 37 patients developed CLAD, only 29 had oscillometry at time of CLAD onset and were included for analysis. These 29 CLAD patients were time-matched with 129 CLAD-free recipients. We performed multivariable regression to investigate the associations between variance in spirometry/oscillometry and the A-score, a cumulative index of ACR, as our predictor of primary interest. Conditional logistic regression models were built to investigate associations with CLAD. Results: Multivariable regression showed that the A-score was positively associated with the variance in oscillometry measurements. Conditional logistic regression models revealed that higher variance in the oscillometry metrics of ventilatory inhomogeneity, X5, AX and R5-19, was independently associated with increased risk of CLAD (p<0.05); no association was found for variance in %predicted FEV1. Conclusions: Oscillometry tracks graft injury and recovery post-transplant. Monitoring with oscillometry could facilitate earlier identification of graft injury, prompting investigation to identify treatable causes and decrease the risk of CLAD.